2017
DOI: 10.21608/asejaiqjsae.2017.3750
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Water Extracts of Phyllanthus emblica and Costus speciousus on Reducing Obesity in Albino Rats

Abstract: Bakground: Obesity is a medical condition in which excess body fat has accumulated to the extent that it may have a negative effect on health, leading to reduced life expectancy and/or increased health problems. Obesity increases the likelihood of various diseases, particularly heart disease, type 2 diabetes, obstructive sleep apnea, certain types of cancer, and osteoarthritis.Obesity is most commonly caused by a combination of excessive food energy intake, lack of physical activity, and genetic susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…On the other hand, our results revealed that SCREE supplementation with NaNO2 has significant and dose-dependent improvements in body weight, body weight gain, and liver weight, while it exhibits insignificant effects on kidney weight compared to the control group. The improvement observed by SCREE treatment is consistent with the studies by abdul-hussein (2019) and Ahmed (Ahmed, 2017) that showed that rats given ethanolic extract of S. costus exhibit significantly (p < 0.05) higher final BW and BWG values compared to the control group. Thyroid hormones play an essential role in growth, development, reproduction, and stress response (Peter, 2011).…”
Section: Evaluation Of the Effect Of Scree On Organ Weight Changes An...supporting
confidence: 90%
“…On the other hand, our results revealed that SCREE supplementation with NaNO2 has significant and dose-dependent improvements in body weight, body weight gain, and liver weight, while it exhibits insignificant effects on kidney weight compared to the control group. The improvement observed by SCREE treatment is consistent with the studies by abdul-hussein (2019) and Ahmed (Ahmed, 2017) that showed that rats given ethanolic extract of S. costus exhibit significantly (p < 0.05) higher final BW and BWG values compared to the control group. Thyroid hormones play an essential role in growth, development, reproduction, and stress response (Peter, 2011).…”
Section: Evaluation Of the Effect Of Scree On Organ Weight Changes An...supporting
confidence: 90%